A nanoscratch method for measuring hardness of thin films. (17th November 2011) - Liu, Sheng; Huang, Han; Gu, Yuantong
Thin solid films were extensively used in the making of solar cells, cutting tools, magnetic recording devices, etc. As a result, the accurate measurement of mechanical properties of the thin films, such as hardness and elastic modulus, was required. The thickness of thin films normally varies from tens of nanometers to several micrometers. It is thus challenging to measure their mechanical properties. In this study, a nanoscratch method was proposed for hardness measurement. A three-dimensional finite element method (3-D FEM) model was developed to validate the nanoscratch method and to understand the substrate effect during nanoscratch. Nanoindentation was also used for comparison. The nanoscratch method was demonstrated to be valuable for measuring hardness of thin solid films.